PENGARUH PENERAPAN PEMBUKUAN KEUANGAN, DAN MANAJEMEN PEMASARAN MODERN TERHADAP KINERJA PELAKU UMKM DI KECAMATAN PUJUT LOMBOK TENGAH - KARTINI, ENDANG; MIMBAR, LALU (Ganec Swara, 2025)
The study aims to determine Financial Bookkeeping, Modern Marketing Management as measured by indicators of preparing an Expenditure Record Book, Income Record Book, making an inventory book, Making a stock book, Digital Marketing, Personalization and Customer Experience, Value-Based Marketing, and Innovation and adaptation have a significant effect both simultaneously and partially on the performance of MSME actors in Pujut District, Central Lombok.The population of 2210 MSMEs and 96 samples. The results of the analysis show that the impact of the eight independent indicators together (partially) and individually (simultaneously) has a significant effect.The regression coefficient also has an impact on improving the performance of MSME actors in Pujut District, Central Lombok. The relationship between the significance of the eight independent and dependent is all stated to be significant so that the efforts of MSME actors to evaluate their business results through the implementation of modern financial and marketing bookkeeping are very influential and improve performance.In the digital era or commonly called modern marketing, not only in urban areas but also reaching remote villages, media have been utilized as supporters in terms of advancing, expanding networks, insights or work links so that the hopes of MSME actors can be realized, namely influencing their work results.The strong or weak correlation between indicators, the results can be shown by the R value of 85.0%, meaning the correlation relationship is very strong.While the Adjusted R Square (R2) is 0.696, this means that 69.6% of the variation in MSME actor performance can be explained by the variation of the eight independent indicators, the rest (100% - 69.6% = 30.4%) is explained by other causes outside the model. Std. Error of the Estimate (SEE) is 0.126. The smaller the SEE value, the more precise the regression model will be in predicting the dependent variable.